Cantonese Loanwords: Conflicting Faithfulness in VC Rime Constraints - Michael J. Kenstowicz (Universitat Autònoma de Barcelona, 2012)
This paper focuses on the ways in which English loanwords are brought into line with four phonotactic constraints that restrict the possible combinations of nuclear vowels and coda consonants in Cantonese Chinese. It is found that three of the four constraints are strictly enforced in loans. Repairs change either the vowel or the coda consonant. Parallel to Mandarin, changes in vowel height features ([high], [ATR]) as opposed to changes in vowel backness are employed. Coda consonant changes obey a dorsal > coronal > labial faithfulness hierarchy that mirrors the typology of coda mergers discovered by Chen (1973) for many Chinese dialects. While changes in both the vowel and coda consonant occur, on-line adaptations favor changing the coda and preserving the vowel and suggest that the relative phonetic salience of the nuclear vowel to the coda consonant still plays a role in these adaptations.